Spectrometric and Chromatographic Profiling of Naringin from Citrus reticulata Blanco, Native to the Himalayan Region of Darjeeling and Sikkim - Baraily, Vishala Rani; Shrestha, Bhupendra; Mandhadi, Jithendar Reddy (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim: Citrus reticulata Blanco (CRB), widely cultivated in the Himalayan regions of Darjeeling and Sikkim, is a remarkable source of bioactive flavonoids, particularly naringin. This study presents the methodical effort to isolate, characterize, and quantify naringin from CRB grown in the foothills of the Himalayan region of Darjeeling and Sikkim where such data have not been reported earlier to the best of our knowledge, emphasizing the impact of agro-climatic conditions and elevation on phytochemical profiles. Materials and Methods: Juice and Peel extracts were examined using a mixed Chromatographic (TLC, HPTLC, HPLC) and Spectroscopic (UV, IR, NMR, MS) methods on samples gathered from various altitudinal sites. The Rf and retention time values of the isolated chemicals closely matched those of the standard, verifying the effectiveness of the extraction and purification performed. Results: Spectral analysis (UV-vis at 282 nm, IR, 1H-NMR., 13C-NMR and mass spectrometry) established a strong foundation for the identity and structure of the compound. Notably, the detected concentrations of naringin in the Himalayan region CRB were significantly higher than those documented for citrus grown in the different geographical areas, indicating that elevation and agro-climatic factors enhance the phytochemical compositions. Conclusion: Thus, this robust analytical approach gives firm information regarding the accuracy of the techniques, which helped in the quality and quantity assessment of naringin in the Himalayan CRB. While the study discusses the pharmacological relevance of naringin, the scope does not extend to drug interaction experiments.
Keywords: Citrus reticulata Blanco; Darjeeling; Naringin; Plant compound evaluation; Sikkim